Native Digitals and Parental Adaptation in the World of Education - Triawanto, Yugo (Proceeding International Conference on Lesson Study, 2023)
IT-based learning is a concept that has been around for a long time in the world of Indonesian education. In fact, information technology has penetrated various educational domains, from higher education to early childhood education. However, what is of concern is the extent to which the use of IT is implemented in the education sector. This research is needed because today’s students are Native Digitals and Gen Z or the millennial generation and are also sometimes known as the quota-eating generation. Teachers and school elements need to think about and take real action in implementing IT implementation in learning. This research was conducted using a quantitative research paradigm. Where this research examines a certain population or sample and collects data using a research instrument in the form of a questionnaire. The data analysis carried out was quantitative deductive. This research was conducted on students and parents of classes 7ICP, 7A, 7B, and 7C at SMP Muhammadiyah 12 GKB Gresik with a total of 84 respondents who filled out the questionnaire out of 123 total respondents. The results of this research were that 68.29% of respondents cared about the learning improvement process. 60.7% of students were happy and 23.8 students were very happy with online assignments which was in line with 69% of students’ parents being happy with online assignments. The response of being happy with PTS Online was 33.3% while very happy with PTS Online was 29.8%, a smaller percentage than Online Assignments. 69% of students’ parents are happy with Online Homework.